ANALISIS PENGARUH INFLASI, BI RATE DAN NILAI TUKAR TERHADAP PERTUMBUHAN PENDAPATAN PERBANKAN DI BEI PERIODE 2017 – 2020 - Michelle michelle (Akuntansi Prima, 2022)
The purpose of this study to examine and analyze the effect of inflation, BI rate, value exchange andOperating Expenser Operating Income on Revenue Growth Banking on the IDX for the period 2017 - 2022.This search is a descriptive study. The population of this study is all banks listed on the Indonesia StockExchange as many as 45 companies. The research sample used purposixe sampling technique in order toobtain the number of a sample of 27 companies. The statistical method used in regression analysis multiplelinear. The results showed that partially stated inflation and Operating Expenses Operating Income has asignificant effect on growth banking income listed on the IDX for the period 2017 – 2020 while the BI rateand Exchange rate has no effect and is not significant on income growth banks listed on the IDX for theperiod 2017 – 2020. And also simultanaeously state Inflation, Bi rate, Exchange rate and OperatingExpenses Operating Income has an effect sihgnificantly to growth banking revenues listed on the IDX forthe period 2017 – 2020. The conclusion of this study is simultaneously and partially Inflation adn ExpensesOperational Operating Income has a significant effect on growth banking income listed on the IDX for theperiod 2017 – 2020.